REDUCING PEROXIDE VALUE IN USED COOKING OIL USING AMPO AS AN ADSORBENT - S. Susilowati; Khanza Lolita Astya; Ulinnuha Syaiful Bachri (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2021)
Cooking oil can only be used two or three times, more than that the oil is deemed unsuitable and can harm our health. The reason is, every time the cooking oil is used for frying, an oxidation reaction that is triggered by heat occured and causes the chemical chain bonds in cooking oil become unstable and forms hydroperoxides. The hydroperoxide found in used cooking oil increases the peroxide value. In which, the suitability of cooking oil is based on the peroxide value. In order to reduce the peroxide value in used cooking oil, in this study, Ampo is used as an adsorbent to adsorb the peroxide compound. The procedure used in this study includes a preliminary analysis of the used cooking oil to determine the initial peroxide value. After that, the Ampo adsorbent is activated with 1N Citric Acid to open the pores on the surface of the Ampo. Activated Ampo will then be mixed into 200 ml of used cooking oil with a magnetic stirrer with a stirring speed of 300 rpm and with a temperature of 50oC. The adsorption process was carried out by varying the mass variables of Ampo into 70, 75, 80, 85, and 90 grams, and stirring time of 30, 60, 90, 120, and 150 minutes. After the adsorption process is completed, the cooking oil that has been filtered by the Ampo adsorbent will be analyzed to get the final peroxide value. By knowing the peroxide value before and after the adsorption process, the adsorption isotherm can be calculated. The adsorption process of used cooking oil with Ampo adsorbent proved to reduce the peroxide value, in which stirring times and adsorbent masses were the influential variables in the study. The best result was obtained with 60 minutes stirring time and mass of 75 grams. This condition provided a peroxide value of 0.99 meq/kg, which means that there was a decrease in the peroxide value by 93%. This result is in accordance with the provisions of SNI 3741-2013, with a maximum peroxide value of 10 meq/kg. The maximum adsorption capacity in this study was obtained from the Freundlich equation of 14.6487 mg/gram.